If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3(x + 4) = 0 Reorder the terms: x + 3(4 + x) = 0 x + (4 * 3 + x * 3) = 0 x + (12 + 3x) = 0 Reorder the terms: 12 + x + 3x = 0 Combine like terms: x + 3x = 4x 12 + 4x = 0 Solving 12 + 4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 4x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 4x = 0 + -12 4x = 0 + -12 Combine like terms: 0 + -12 = -12 4x = -12 Divide each side by '4'. x = -3 Simplifying x = -3
| u+15=2+3u | | 4x-2=11x+5 | | z^2+3z-28=0 | | z+19=84 | | 5x+234=25x+7 | | -5x^2-45x-100=0 | | z/12+19=84 | | 12/0.5= | | 4(x+1)=8(2x-3) | | -1+-6x=8-9x | | (x+17)=0 | | 7x-4=2x+15 | | 3/8+9x-1/2 | | z=2/7 | | k^2+11k+28=0 | | 120.5= | | 5(x-3)(x+4)=0 | | 7y-39=3y-11 | | 2.2*x^2=6 | | 12x=3x^1 | | -180-10=10x+20 | | 10x+6=12x-3 | | 12c=73 | | 7=6q+8/4 | | 1/6t^2-36=0 | | -2/3+1/9+4/15 | | 12/0.5 | | 2a^2+72=0 | | 6x+6=14x-1 | | x+10+40-x=180 | | 2000-150P=500+50P | | -2/3x+1/9x+4/15x |